Magnetically assisted drop-on-demand 3D printing of microstructured multimaterial composites - Liu, Wing Chung (2022)
Microstructured composites with hierarchically arranged fillers fabricated by three-dimensional (3D) printing show enhanced properties along the fillers’ alignment direction. However, it is still challenging to achieve good control of the filler arrangement and high filler concentration simultaneously, which limits the printed material’s properties. In this study, we develop a magneti- cally assisted drop-on-demand 3D printing technique (MDOD) to print aligned microplatelet reinforced composites. By performing drop-on-demand print- ing using aqueous slurry inks while applying an external magnetic field, MDOD can print composites with microplatelet fillers aligned at set angles with high filler concentrations up to 50 vol%. Moreover, MDOD allows multimaterial printing with voxelated control. We showcase the capabilities of MDOD by printing multimaterial piezoresistive sensors with tunable performances based on the local microstructure and composition. MDOD thus creates a large design space to enhance the mechanical and functional properties of 3D printed electronic or sensing devices using a wide range of materials.